Graphene oxide‐based noble‐metal nanoparticles composites for environmental application. (April 2021) - Yang, Wenshuai; Pan, Mingfei; Huang, Charley; Zhao, Ziqian; Wang, Jianmei; Zeng, Hongbo
Abstract: Noble metal nanoparticles (NPs)-based materials have been widely applied in various environmental applications, including the catalytic reduction of organic pollutants and elimination of the microbial pathogens in wastewater due to its unique physicochemical properties. However, the stability and catalytic activity of NPs-based materials are limited due to their severe aggregation in aqueous environments. Recently, graphene oxide (GO), a 2D material with large specific surface area, has been used as a platform to load NPs as a NPs@GO nanocomposite with enhanced catalytic performance and stability. In this review, we focus on the discussion about the recent progress in the synthesis methods and properties of NPs@GO nanocomposites, recyclability of NPs@GO nanocomposites, and applications of the NPs@GO nanocomposites in catalytic reduction of organic pollutants and elimination of microbial pathogens in wastewater as well as the corresponding catalytic and antibacterial mechanisms. Finally, we conclude with perspectives on the remaining challenges as well as the recommendations for future development in this field. Highlights: 1.Recent advances in the design and synthesis of NPs/GO nanocomposites for environmental application are discussed. 2.Mechanisms and influence factors of the catalytic performance of NPs/GO nano-catalysts are presented. 3.Limitations and perspectives of the new generation of NPs/GO nanocomposites are proposed.